2013
DOI: 10.1371/journal.pone.0082536
|View full text |Cite
|
Sign up to set email alerts
|

Reconstitution of Cholesterol-Dependent Vaginolysin into Tethered Phospholipid Bilayers: Implications for Bioanalysis

Abstract: Functional reconstitution of the cholesterol-dependent cytolysin vaginolysin (VLY) from Gardnerella vaginalis into artificial tethered bilayer membranes (tBLMs) has been accomplished. The reconstitution of VLY was followed in real-time by electrochemical impedance spectroscopy (EIS). Changes of the EIS parameters of the tBLMs upon exposure to VLY solutions were consistent with the formation of water-filled pores in the membranes. It was found that reconstitution of VLY is a strictly cholesterol-dependent, irre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(28 citation statements)
references
References 46 publications
1
26
1
Order By: Relevance
“…Similar EIS response was observed for other pore-forming toxins such as αHL [28,29] and vaginolysin [9]. cholesterol, already performed in literature [30].…”
Section: Electrochemical Impedance Of Tblms Is Affected By Rplosupporting
confidence: 83%
See 2 more Smart Citations
“…Similar EIS response was observed for other pore-forming toxins such as αHL [28,29] and vaginolysin [9]. cholesterol, already performed in literature [30].…”
Section: Electrochemical Impedance Of Tblms Is Affected By Rplosupporting
confidence: 83%
“…The relevance of the importance of further studies of tBLMs is underlined by the recently reported reconstitution of membrane proteins in artificial membrane systems [49] creating an ideal platform for exploring their potential for pharmacological or biotechnological uses. Different version of lipids have been used as model building blocks to generate membranes homologue, as vesicular structures in solution (liposomes) [50], or as, tethered bilayer membrane, already tested against different toxins [9,29,51], in nanoparticle studies [52] and with soluble amyloid-beta oligomers [39]. Further improvements could be still reached related to the sensitivity of tBLMs with more detailed studies on the characteristics and properties of anchor molecules, a field continuously developing.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the absence of cholesterol no effect of VLY on tBLMs was detected (9). On the other hand, mutated variants of VLY or antibody treated preparations of recombinant VLY did not affect membrane integrity even in the presence of cholesterol (9).…”
Section: Vly Increases Defect Density Only In Tblms Containing Cholesmentioning
confidence: 94%
“…12,13 Namely, tethered bilayer lipid membranes (tBLMs) are solid-supported, two-dimensional phospholipid systems which can be fabricated to closely mimic the fluid and chemically heterogeneous environment of the biological membrane, 14,15 and are well-established for investigating both peripheral and integral membrane protein interactions with a bilayer. [16][17][18][19] Delivering IMPs into the tBLMs have been performed by a number of methods, from directly synthesizing the protein in the presence of the tBLM in vitro, 9 to transferring expressed and refolded proteins from membrane-mimetic surfactants, detergents, or amphipols. 10,12,13 As a reductionist approach, synthesizing peptides comprised mainly of the TM domain of model receptor proteins offers a less complicated method for membrane deposition and biophysical characterization of integrated TM domains of model surface receptors.…”
Section: Introductionmentioning
confidence: 99%